A randomized controlled trial comparing short-term versus long-term catheterization after vaginal prolapse surgery - Thakur, Nupur; Gurung, Geeta; Rana, Ashma (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Aim: To determine whether short term bladder catheterisation for 24 hrs after vaginal hysterectomy for prolapse would be more advantageous to routinely practiced 3 days catheterisation. Method: Randomized comparative study was done as thesis topic in Gynaecological Ward of TU Teaching Hospital, Maharajgunj, Kathmandu from 30th October 2004 to 2nd November 2005. A total of 100 women were included in this study. Prior to surgery at OT table, and before giving prophylactic antibiotics urine samples were collected from metal catheter for routine analysis. They were randomized into two groups. In groups 1 (n=50) transurethral catheter was removed after 24 hrs of surgery. In group 2 (n=50) catheter was removed on 3rd post operative day. Urine culture was taken before removal of the catheter. Residual volume of urine after the first voiding was measured by transabdominal ultrasound. Recatheterisation for three more days was considered whenever residual volume exceeded 200ml. Result: Recatheterisation was not needed in either groups for residual volume >200ml. Regarding recatheterisation 4 needed them after 2-3 hrs of first voiding. Among these 4 women, cause of urinary retention was accountable for pelvic haematoma leading to pelvic abscess in one case, which belonged to group 1 where as urinary tract infection was responsible for urinary retention in group 2. There were no explainable causes in two cases. But urinary tract infection was seen in two cases in group 1 and 11 cases in group 2 (P value 0.017). Conclusion: This study has shown that short term catheterisation is more beneficial in terms of lower incidence of urinary tract infection (2 Vs 11) and related febrile morbidity as compared to long term catheterisation. Key words: Uterovaginal prolapse, pelvic floor repair with vaginal hysterectomy, catheterisation. doi:10.3126/njog.v2i1.1473 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 29 - 34 May -June 2007